Healing independent elderly village in Kota Kinabalu, Sabah - Fazeree, Muhamad Irphan; Aripin, Srazali; Abdul Rahim, Asiah (Kulliyyah of Architecture and Environmental Design (KAED) International Islamic University Malaysia, 2025)
As Malaysia’s ageing population continues to rise, many elderly individuals particularly in Kota Kinabalu face challenges such as loneliness, declining health and inadequate care environments. Existing facilities often lack cultural sensitivity, emotional warmth, and proper support for independence, leading to isolation and loss of dignity. This thesis proposes a new architectural response through the design of Walai Healing Elderly Village, inspired by traditional Sabahan house typologies such as the Rumah Bajau, Rumah Dusun Lotud, and Rumah Panjang Rungus. The proposal integrates universal design standards, passive environmental strategies, and healing landscapes to promote autonomy, cultural belonging, and social connection. The aim is to create a healing environment that enhances well-being by embracing the cultural familiarity, nature, and the community living.